Short-term effects of clown visits in child and adolescent psychiatric care: a pilot study on patient stress and mood outcomes and staff evaluations - Friedrich, Amos-Silvio Erik; Holzmeier, Lorena; Ehlers, Johanna; Seebacher, Simone; Rössler, Maggie; Skoluda, Nadine; Nater, Urs Markus; Zemp, Martina (Frontiers in Psychiatry, 2025)
BackgroundClown visits are an effective intervention to alleviate patients’ stress and anxiety in pediatric hospital settings. However, while children and adolescents in inpatient psychiatric treatment might uniquely benefit from healthcare clowning, little research has addressed the effectiveness of clown visits in this setting.MethodThis pilot study examined the short-term effects of clown visits on psychological (self-reported stress and mood) and physiological (salivary cortisol) outcomes in 29 children and adolescents aged between 7 and 17 years (M = 12.69, SD = 2.90) in a noncontrolled repeated pre-post design over 4 weeks. In addition, 21 care staff members reported separately on their perceived impact of clown visits.ResultsSelf-reported stress levels of children and adolescents were decreased significantly from before to after clown visits, whereas salivary cortisol indicated a similar, but nonsignificant decrease. According to the Multidimensional Mood Questionnaire (MDMQ), patients showed significant improvements in energetic arousal, but there were no effects on mood valence and calmness. The effectiveness of the clown visits did not change over repeated visits. Care staff reported that clown visits had a positive impact on patients’ and their own well-being, but their evaluations regarding their stress levels and work processes on the ward were mixed.DiscussionThe present results provide preliminary evidence that the stress-reducing and energizing effects of clown visits, which previous studies have demonstrated in various pediatric settings, can also be transferred to the field of inpatient child and adolescent psychiatry. Mixed self- and work-related evaluations from care staff suggest that improvements in the implementation of clown visits could help eliminate disruptive elements of this intervention.